Handbook of research on solving societal challenges through sustainability-oriented innovation - Carvalho, Luisa Cagica 1970-; Bogas, Paulo 1970-; Kneipp, Jordana 1986-; Avila, Lucas 1988-; Ossmane, Elis 1980- (IGI Global, 2023)
This book is intended to be an essential reference source that emphasizes the importance of innovation and sustainability as a possible solution for the big challenges of our society, leveraging the articulation between innovation and sustainability with the big challenges that our existence are facing today and in the near future